Marx in motion : a new materialist Marxism - Nail, Thomas (New York, NY : Oxford University Press, 2020)
"Socialism is back and with it is a renewed interest in Marx's critique of capitalism. After the 2008 financial crash international book sales of Capital exploded for the first time in decades. In a world of rising income inequality, right-wing nationalisms, and global climate change, people are again looking to the father of modern socialism for answers. This book is written to help those returning to Marx today get answers to their pressing questions about the nature of wealth, ecological crisis, gender inequality, colonialism, migration, and the possibility of socialism. Marx, as always, remains our contemporary. This book also offers readers a new perspective on a several major ideas in Marx's work. It argues that Marx, contrary to convention, did not think history was deterministic or that reality could be reduced to classical materialism. Marx was not an anthropocentric humanist nor did he have a labor theory of value. The unique contribution of this book is that it begins with Marx's earliest and most neglected book on ancient naturalism in order to show its lasting methodological effect on his "process materialism" defined by the primacy of motion. This "kinetic Marxism," as I call it, offers us a new way to re-read Capital that bears directly on a number of contemporary issues. This also makes Marx in Motion the first book to offer a new materialist reading of Marx. The result of all this is a fresh new view on the important theories of primitive accumulation, metabolism, value, fetishism, dialectics, and the possibility of a kinetic communism for the 21st century"--
Includes bibliographical references and index.
Keywords: Philosophy, Marxist; Socialism